Microbiology : a human perspective - Nester, Eugene W; Roberts, C. Evans; Nester, Martha T (Wm.C. Brown, 1995)
This text utilizes the organ system approach and emphasizes the relevance of microbiological principles to human health, as well as providing a historical background. There are chapter-specific study cards included that feature key diseases and microorganisms.
Keywords: mikrobiologie, lékařská mikrobiologie; mikrobiologie; Microbiology